PENENTUAN KUALITAS BATU BATA MERAH BERDASARKAN KONDUKTIVITAS TERMAL - Rika Utari; Sugianto '; Erman Taer (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A compressive strength testing (  ) and thermal conductivity testing (k) havebeen performed on red bricks from the district of Tenayan Raya and Rumbai. Thisresearch using a compression machine, iron, solder, thermometer, styrofoam and itspurpose was to prove the theory of the thermal conductivity having relationship tocompressive strength. The result showed that the highest compressive strength due tothe conventional red brick of Rumbai district is 10.82 x 10 5 N/m 2 and the lowestcompressive strength due to the press red brick of Tenayan Raya district is 3.67 x 10 5N/m 2 . The research results of thermal conductivity showed that the thermal conductivityvalue of the best sample of conventional red brick of Rumbai district is 1.05 J/sm  C andthe thermal conductivity value of the lowest sample of press red brick of Tenayan Rayadistrict is 0.857 J/sm  C . The affecting factor of the quality of red bricks is density. Thedensity of conventional red bricks of Rumbai district for compressive strength andthermal conductivity, are 2486.880 Kg/m 3 and 2200 Kg/m 3 , respectively. Meanwhileaverage density of press red brick of Tenayan Raya district for compressive strength andthermal conductivity are 1696 Kg/m 3 and 2000.5 Kg/m 3 , respectively. Based on theresult there was in relationship between compressive strength and thermal conductivitywhich was discribed by the regression equation Y  2 x 10  7 X  0 . 812